Are pollinators the agents of selection on flower colour and size in irises?. Issue 6 (2nd January 2018) - Souto‐Vilarós, Daniel; Vuleta, Ana; Jovanović, Sanja Manitašević; Budečević, Sanja; Wang, Hui; Sapir, Yuval; Imbert, Eric
Abstract : Plant–pollinator interactions are believed to play a major role in the evolution of floral traits. Flower colour and flower size are important for attracting pollinators, directly influencing reproduction, and thus expected to be under pollinator‐mediated selection. Pollinator‐mediated selection is also proposed to play a role in maintaining flower colour polymorphism within populations. However, pigment concentrations, and thus flower colour, are also under selective pressures independent of pollinators. We quantified phenotypic pollinator‐mediated selection on flower colour and size in two colour polymorphic Iris species. Using female fitness, we estimated phenotypic selection on flower colour and size, and tested for pollinator‐mediated selection by comparing selection gradients between flowers open to natural pollination and supplementary pollinated flowers. In both species, we found evidence for pollen limitation, which set the base for pollinator‐mediated selection. In the colour dimorphic Iris lutescens, while pigment concentration and flower size were found to be under selection, this was independent of pollinators. For the polymorphic Iris pumila, pigment concentration is under selective pressure by pollinators, but only for one colour morph. Our results suggest that pollinators are not the main agents of selection on floral traits in these irises, as opposed to the accepted paradigm on floral evolution. This study provides an opposing example to the largely‐accepted theory that pollinators are the major agent of selection on floral traits.